Energy Harvesting Enabled NOMA Systems With Full-Duplex Relaying - Guo, Cheng; Zhao, Liqiang; Feng, Chen; Ding, Zhiguo; Chen, Hsiao-Hwa (IEEE transactions on vehicular technology, 2019)
This paper investigates an integrated wireless communication system including non-orthogonal multiple access, full-duplex relaying, and energy harvesting techniques (named as EH-FD-NOMA). In this scheme, an energy-limited full-duplex relay harvests energy from a source at the first stage. Then, the relay detects the superimposed signal from the source and transmits the decoded signal to destination. Closed-form outage probabilities and ergodic rates at the relay and destination are derived. Numerical results verify the analytical results and show the superior performance of the EH-FD-NOMA if compared to its counterparts.